PENGARUH SIKAP PERCAYA DIRI SISWA TERHADAP HASIL BELAJAR SUBTEMA LINGKUNGAN DAN MANFAATNYA - Rais Hidayat; Niken Kurniawati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
ABSTRACT Niken Kurniawati 037118175. The Influence of Students' Self-Confidence Against Learning Outcomes of the Environmental Subtheme and Its Benefits. Elementary School Teacher Education Study Program. Faculty of Teacher Training and Education. Pakuan University 2022. The purpose of this study was to determine the effect of students' self-confidence on learning outcomes in the environmental subtheme and its benefits. The population in this study were students of class V-A and V-B Pajajaran State Elementary School, Bogor City. The analysis prerequisite test technique is in the form of a normality test, then homogeneity testing is carried out. The data that were declared normal and homogeneous were used to test the hypothesis, the results of which showed that there was an influence of students' self-confidence on the learning outcomes of the environmental subtheme and its benefits. The simple correlation regression analysis technique produces a relationship model which is expressed in the form of a regression equation, namely = 48.50 + (0.42) (X). The results of this study are shown by statistical analysis which produces a correlation coefficient (rxy) of 0.45. While the coefficient of determination is 20.7%. Regression analysis technique and simple correlation of the effect of students' self-confidence on learning outcomes of the environmental subtheme and its benefits produce an effect which is expressed in the form of a regression equation, namely = 48.50 + (0.42) (X), which means every increase in the unit of trust self causes an increase in student learning outcomes by 0.42 units. Based on the results of the research above, it can be concluded that there is a positive influence between students' self-confidence towards the learning outcomes of the environmental subtheme and its benefits in grades V-A and V-B of the Pajajaran State Elementary School, Bogor City, for the 2022/2023 academic year.